CLINICAL CRITERIA FOR DRUG SELECTION IN THE TREATMENT OF VIRAL INFECTIONS IN CHILDREN - O`ktamova N.B,; Boymuratov F.T, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: Viral infections are among the most common causes of morbidity in the pediatric population and represent a major challenge for clinicians worldwide. The selection of appropriate antiviral or supportive therapy in children requires careful consideration of several clinical criteria, including the type of virus, age-related pharmacokinetics, immune status, and potential drug toxicity. Since many viral infections are self-limiting, unnecessary medication use—particularly antibiotics—should be avoided. Rational drug selection must balance therapeutic efficacy and safety while minimizing adverse reactions and resistance development. This study reviews the main clinical factors that influence drug choice in pediatric viral infections and emphasizes the importance of evidence-based, individualized pharmacotherapy to ensure optimal outcomes and reduce complications.